Reprodução Induzida de Lambari (Astyanax Lacustris) Utilizando Diferentes Indutores Hormonais - SANTOS, Jussara Garrido,; COSTA, Deliane Cristina,; TAVARES, Tainara Vieira,; WANDERLEY, Alysson Martins,; CAMPOS, Cristiane Meudal de,; FERRAZ, André Julien, (ANAIS DO ENIC, 2024)
-